Restoratif Justice dalam Wawasan Pemidanaan menurut Adat Gayo - Mohd. Din (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: The advance of thery regarding the purpose of criminal punishment was started from Kantianism, retributive and utilitarian which has orientation toward the crime actor. Basically, this aim does not accomodate integrated criminal punishment purpose, untuil emergin restroaktive concept in which involve the crime victim interest in the crime punishment mechanism. For Indonesia, restroaktive justice concept has been kwon in the curtomary law under the peace process.  Restroaktif Justice in the Insight of Criminal Punishment according to Gayo’s Customary Law